Conceptual implementation to access the extend of influence of lightning electromagnetic radiation on mobile radio communication - Mohd. Esa, Mona Riza (2005)
In this paper, the research of interference to the private mobile radio (PMR) due to lightning electromagnetic field has been done. The conceptual implementation to access the extend of influence of lightning electromagnetic radiation (LEMR) on mobile radio communication. Wireless data has been transmitted through a pair of Motorola Talkabout T5420 walkie-talkie with 14 channels and 38 codes and operates on 14 UHF FRS frequencies. Two types of induced interference has been arranged which are high voltage and high current experiments using impulse voltage generator (IVG) and recloser test set (RTS) in high voltage laboratory, Institute of High Voltage and High Current, UTM.